Practice of street clinic professionals in the context of Primary Health Care in Brazil: A scoping review (Research, Society and Development, 2021)
Objective: to map in the national scientific literature the productions related to the performance of the Consultório na Rua (CnaR) professionals in the scope of Primary Health Care (PHC) in Brazil. Method: This is a scope review that followed the recommendations proposed by the Joanna Briggs Institute's Evidence Manual (JBI). The application of the Population, Concept, Context (PCC) strategy culminated in the following research question: "What is known about the performance of CnaR professionals in the context of PHC in Brazil?". The search took place between December 2020 and January 2021, using the descriptor “Consultório na rua”. After applying the eligibility criteria, thirteen studies were selected. In the extraction of data, the instrument proposed by JBI was used. Results: The sample consisted of thirteen studies. For better understanding, the mapped studies were organized into axes, namely: health care; articulation with the devices of the Health Care Networks and Intersectoral Networks; lightweight care technologies; harm reduction; and teamwork. Conclusion: The total number of publications included in this scope review shows that the topic under study has been little discussed. In this context, given the findings, there is a demand for research aimed at elucidating the performance of CnaR professionals. The results of the study promote innovation, dissemination and dissemination of this theme that is of great relevance to public health in Brazil, since it lists and maps the performance of these professionals.